OVERVIEW ON CARBONDOTS - SINHA, PRIYANKA; RATHNAM, GRACE; S. M., DAN KASPERO; N., JAGAN KARTHICK (International Journal of Current Pharmaceutical Research, 2023)
As a prospective material for biosensing, drug administration, and bioimaging, carbon dots (C-dots) have grown in popularity due to their outstanding visual characteristics, great biocompatibility, and low cytotoxicity. As a result, there has been a lot of curiosity about the development, characteristics, and potential applications of CDOTs. Based on variations in precursors and methods of preparation, CDOTs were divided into two classes. The procedure for the formation of CDots was outlined, and their luminescence process was investigated. Also presented were CDOTs' uses in biosensing, medication administration, and bioimaging. For their continued development, CDOTs' challenges and challenges were reviewed.